PENGARUH HARGA, KUALITAS LAYANAN DAN TEKNOLOGI E-COMMERCE TERHADAP KEPUTUSAN UNTUK MENGGUNAKAN LAYANAN GO-JEK DI WILAYAH KECAMATAN CIBINONG - Ilyas, Yasnimar (Economicus, 2018)
In this era, some people use E-commerce for online transportation. Go-Jek is one of the alternatif online transportation that used by people. The aim of the research is to know the effect of factor cost, quality of services, and E-Commerce technologi to decision for using Go-Jek service in Kecamatan Cibinong. The type of research is used correlational research. The data analysis is used linear regression of multiple with helping SPSS program version 17.0. Result of the research shows the test linear regression of multiple obtained the regression equation is: Y = 3.340+ 0,631X1+ 0,180X2+ 0,678X3. The meaning is every it increases the values of free variable (cost, quality of services, and E-Commerce) so it will increase the value of customers decision using Go-Jek in Kecamatan Cibinong. The results of the coefficient of determination show that the value Adjust R Square of 0,446 (44,6%) Which means together factors cost , the quality of services and E-Commerce have contribution or affecting decision to use Go-Jek in Kecamatan Cibinong of 44,6 %, while the rest 55,4% affect by the other factors that is not discussed in the research. The results of the hypothesis whether partial and simultaneously Prove that factors price , the quality of services and e-commerce affect decision costumers using Go-Jek in Kecamatan Cibinong. The most dominant factors affecting decision to using go-jek in Kecamatan Cibinong is a factor information technology E-Commerce , this is proven by value the regression coefficient of 0,678.